Arctic Ocean outflow shelves in the changing Arctic: A review and perspectives. (December 2015) - Michel, Christine; Hamilton, Jim; Hansen, Edmond; Barber, David; Reigstad, Marit; Iacozza, John; Seuthe, Lena; Niemi, Andrea
Highlights: Arctic outflow shelves are undergoing major hydrological and cryospheric changes. The Arctic outflow shelves respond differently to climate and ecosystem forcings. Model scenarios identify current and future productivity regimes. The contribution of outflow shelves to Arctic primary production is underestimated. Abstract: Over the past decade or so, international research efforts, many of which were part of the International Polar Year, have accrued our understanding of the Arctic outflow shelves. The Arctic outflow shelves, namely the East Greenland Shelf (EGS) and the Canadian Arctic Archipelago (CAA), serve as conduits through which Arctic sea ice and waters and their properties are exported to the North Atlantic. These shelves play an important role in thermohaline circulation and global circulation patterns, while being influenced by basin-scale and regional changes taking place in the Arctic. Here, we synthesize the current knowledge on key forcings of primary production and ecosystem processes on the outflow shelves, as they influence their structure and functionalities and, consequently their role in Arctic Ocean productivity and global biogeochemical cycles. For the CAA, a fresh outlook on interannual and decadal physical and biological time-series reveals recent changes in productivity patterns, while an extensive analysis of sea ice conditions over the past 33 years (1980–2012) demonstrates significant declines in multi-year ice and a redistribution of ice types. For the EGS, our analysis shows that sea ice export strongly contributes to structuring spatially diverse productivity regimes. Despite the large heterogeneity in physical and biological processes within and between the outflow shelves, a conceptual model of productivity regimes is proposed, helping identify general productivity patterns and key forcings. The different productivity regimes are expected to respond differently to current and future Arctic change, providing a useful basis upon which to develop predictive scenarios of future productivity states. Current primary production estimates for both outflow shelves very likely underestimate their contribution to total Arctic production.